Standard Errors in Jumlah Ismīyah Phrases: Analysis of Arabic Thesis on Indonesian Undergraduate Students | Al-Akhthā Al-Syāi - Ni'matun Najah; Lailatul Qomariyah; Wahyuddin Wahyuddin; Ade Destri Deviana (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2022)
In learning Arabic, students often make language errors influenced by their first language interference in learning the target language. Therefore, it is necessary to analyze language errors to minimize students' language errors and to know the material that needs in-depth study. This research talks about the common errors in the nominal sentence structure in scientific research. This research aims to know the types of common linguistic errors in the formation of sentence structure patterns in nominal sentence among students of the Arabic Language Education Department. The research method used is library research, meaning that the data collection derives from a summary of scientific research, and the technique used to analyze data is error analysis. The research results show that the common mistakes in sentence structure patterns were found in several student thesis abstracts, including the suitability of mubtada+khabar in its type, the interference of mother tongue in learning the target language, and the specificity of mubtada'. The results of this study serve as reflection and reference for teachers to explain the jumlah ismiyah material.